Product Differentiation of Colenak Jam as a Local Specialty of Tasikmalaya - Ridwan Iskandar; Cytra Amalia Hadian; Risya Ladiva Bridha (Gastronomy Tourism Journal, 2023)
This study aims to make jam products with colenak flavor as a Tasikmalaya specialty. Another purpose of this study is to preserve colenak as a traditional West Javanese specialty that are now rarely found. In addition, this study also aims to raise public awareness about colenak which is currently not very well known. This research is also expected to increase the interest of the community in colenak and can be enjoyed by people in all generations. This study used an experimental method by experimenting three different recipe formulations, namely the use of colenak 35% of the total ingredients and mashed peanut (SC 1), the use of colenak 50% of the total ingredients and coarsely chopped peanut (SC2), the use of colenak 75% of the total ingredients and very coarsely chopped peanut (SC 3). The method used in this study is an experimental by conducting organoleptic tests and consumer acceptability tests. Organoleptic tests were carried out on 10 trained panelists and consumer acceptability tests were carried out on 40 consumer panelists. The results of organoleptic tests showed that the colenak jam recipe formulation SC3 was the most preferred product with an average value of 3.53. Then the results of the consumer acceptability test showed an average value of 4.15 from a value scale of 1-5 which means that respondents or consumer panelists of the product agreed if the product could be accepted by consumers. Thus it can be concluded that colenak jam products with SC3 recipe formulations can be promoted as Tasikmalaya specialty that can be accepted by the public.